2015
DOI: 10.1016/j.ijrobp.2015.07.1915
|View full text |Cite
|
Sign up to set email alerts
|

LIMD1 Radiosensitizes Human Non-Small Cell Lung Cancer Cells Via Inhibiting NF-kB Signaling

Abstract: with PI-103 showed persistent gH2AX foci, indicating delayed repair of DNA strand breaks. PI-103 alone increased levels of poly(ADP-ribose) and phosphorylated extracellular signal-regulated kinase, and downregulated BRCA1. Conclusion: Combined use of olaparib and PI-103 enhanced radiationinduced cell death in BRCA-proficient MDA-MB-435S and MDA-MB-231-BR cells and xenografts. TNBC patients have high incidences of locoregional relapse and distant metastasis, and radiation therapy targets both locoregional contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It represses the anti-oncogenic Hippo pathway by antagonizing YAP1 phosphorylation [ 11 , 69 ], and promotes ubiquitination-mediated HIF1α degradation by interacting with the tumor suppressor VHL [ 9 , 10 ]. It is also downregulated, and inhibits NFκB activity and autophagic cell death, in human non-small cell lung cancer cells [ 12 ]. Surprisingly, its expression is positively correlated with expression of the oncogene IRF4 in EBV latency, and it is required for LMP1 oncogenic functions and its depletion promotes DNA damage and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It represses the anti-oncogenic Hippo pathway by antagonizing YAP1 phosphorylation [ 11 , 69 ], and promotes ubiquitination-mediated HIF1α degradation by interacting with the tumor suppressor VHL [ 9 , 10 ]. It is also downregulated, and inhibits NFκB activity and autophagic cell death, in human non-small cell lung cancer cells [ 12 ]. Surprisingly, its expression is positively correlated with expression of the oncogene IRF4 in EBV latency, and it is required for LMP1 oncogenic functions and its depletion promotes DNA damage and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…LIMD1 is involved in the assembly of numerous protein complexes by acting as an adaptor protein that interacts with various proteins such as Rb [ 6 ], TRAF6 [ 7 ], p62/SQSTM1 [ 8 ], VHL and PHD [ 9 , 10 ], and LATS and WW45 [ 11 ], and participates in myriad cellular processes including cell fate determination, cytoskeletal organization, osteoclastogenesis [ 8 ], repression of gene transcription, cell-cell adhesion, cell differentiation, proliferation and migration. Interaction of LIMD1 with TRAF6 enhances the ability of TRAF6 to activate AP1 and negatively regulates the canonical Wnt receptor signaling pathway in osteoblasts [ 7 ], and interaction with p65 negatively regulates NFκB activity in human non-small cell lung cancer cells [ 12 ]. Our previous study has shown that LIMD1 and IRF4 expression levels positively correlate in different hematological malignancies, including EBV-associated lymphomas [ 13 ].…”
Section: Introductionmentioning
confidence: 99%